Robust H∞ Control for Spacecraft Rendezvous with a Noncooperative Target - Shu-Nan Wu; Wen-Ya Zhou; Shu-Jun Tan; Guo-Qiang Wu (The Scientific World Journal)
The robust H∞ control for spacecraft rendezvous with a noncooperative target is addressed in this paper. The relative motion of chaser and noncooperative target is firstly modeled as the uncertain system, which contains uncertain orbit parameter and mass. Then the H∞ performance and finite time performance are proposed, and a robust H∞ controller is developed to drive the chaser to rendezvous with the non-cooperative target in the presence of control input saturation, measurement error, and thrust error. The linear matrix inequality technology is used to derive the sufficient condition of the proposed controller. An illustrative example is finally provided to demonstrate the effectiveness of the controller.